GRID-model of natural agricultural zoning - Shulgan, Roman; Kibukevich, Olena; Yanchuk, Oleksandr; Nikolaichuk, Kateryna (Geodesy and Cartography, 2017)
We have developed IDEF0 model of automated natural agricultural zoning technology based on the research of implementation of natural agricultural zoning, land management automation works with efficient application of new technologies and system approach. The hierarchical model has been developed, determining the weight of the main indicators. To construct GRID-model zoning elementary unit was determined. On the basis of the weights of indicators and obtained values of indicators, weighting coefficients of natural agricultural zoning are calculated and cells of GRID-model are combined according to their weight coefficients in natural agricultural districts by the method of “natural groups”. As a result, we have a new border between Rivne and Ploska-Buderaz natural agricultural districts of Rivne region. To test the need to clarify the limits of natural agricultural districts, we fulfilled normative monetary evaluation of the land, which is located on the border of two natural agricultural districts. As a result of GRID-model use, the normative monetary valuation increased almost 2-fold, resulting from a more detailed consideration of natural conditions of the area. The developed model makes it possible to automate the process of natural agricultural zoning and periodically make adjustments to the limits of districts depending on the change of the lands state and their indicators.